Implementasi Program Corporate Social Responsibility (Csr) Dan Relevansinya Dengan Sustainable Development Goals (Sdgs) Pada Pt Kereta Api Indonesia Divre III Palembang - Viara Meiza; Citra Indah Merina (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2026)
Sustainable development has emerged as a strategic agenda for state-owned enterprises, prompting the alignment of Corporate Social Responsibility (CSR) initiatives with the Sustainable Development Goals (SDGs). In practice, however, the linkage between CSR activities and SDGs indicators is often presented descriptively and lacks systematic assessment. This study examines the implementation of CSR programs and evaluates their relevance to the SDGs at PT Kereta Api Indonesia (Persero) Divre III Palembang, hereafter referred to as PT KAI. Employing a qualitative descriptive design, data were obtained through interviews, field observations, and document analysis, and subsequently examined using the interactive analytical framework of Miles and Huberman. The results demonstrate that PT KAI has implemented CSR initiatives in a structured manner across social, economic, and environmental dimensions. Social programs enhance community welfare and educational access, economic initiatives support local economic empowerment, while environmental activities emphasize conservation efforts and the maintenance of cleanliness within operational areas. Furthermore, the findings indicate alignment with several SDGs, particularly SDG 1, SDG 4, SDG 8, SDG 11, and SDG 13. Nonetheless, the association between CSR programs and specific SDGs indicators has not been systematically formulated. Overall, the study concludes that although CSR implementation has produced tangible benefits, stronger strategic planning and impact-based evaluation are necessary to optimize its contribution to sustainable development.